Joseph Schacht dan Transformasi Hadis Tentang Hukum Islam dalam Konteks Dunia Timur - A. Munawwir; Ani Lestari; Fita Ratu Prilia (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2020)
Hadith studies have not only become the focus of Islamic scholars' attention, but have also become material for orientalist studies. So from this, there are many western scientists and scholars who chose the path of researching hadith. Starting from Ignaz Goldziher to leading scholars of hadith from Germany, Harald Motzki also graces the list of western scholars who are competent in the study of hadith. The long history of hadith in the west is evidence of the proliferation of hadith studies. In contrast to Muslims, western people study hadith departs from their distrust of hadith. Surely this is a different portrait of the traditions of the eastern people. Therefore, various theories and methods they used to justify that the hadith did not come from the Prophet Muhammad, but was made by people after him. This article is in the form of an attempt to explain at length the theory proposed by Joseph Schacht in order to undermine the authenticity of the hadith itself, and some of its weaknesses, which are based on the views of Islamic scholars'.